Letter from George Blight to Margaret M. Booth - Blight, George (1888)
George Blight writes to Margaret M. Booth née Cardeza to inform her of her late husband's date of election to an unspecified academy.
Keywords: Booth, James Curtis, 1810-1888; Martinez Cardeza, Margaret